2004
DOI: 10.1179/000349804225003280
|View full text |Cite
|
Sign up to set email alerts
|

The infectivity and antigenicity ofToxocara caniseggs can be retained after long-term preservation

Abstract: Suspensions of fertilized eggs of Toxocara canis were mixed with 2% neutral formalin and preserved at 4 degrees C. When, after storage for 0, 12, 18, 21 and 24 months, samples of the eggs were incubated at 30 degrees C for 12 days, 96.8%, 92.6%, 74.1%, 51.0% and 19.3% of the eggs in the samples were found to embryonate. The embryonated eggs produced from the fertilized eggs preserved (in 2% neutral formalin at 4 degrees C) for 0, 12, 18 and 21 months were then tested for their infectivity to BALB/c mice, each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Nevertheless, Ayçiçek et al (2001) proved that sodium hypochlorite had no effect on T. canis eggs, thus confirming the results of Juris and Breza (1988). Likewise, at least 50% of the fertilized eggs preserved in 2% neutral formalin at 4°C for 21 months could fully embryonate and then have the same infectivity as embryonated fresh eggs (Chung et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Ayçiçek et al (2001) proved that sodium hypochlorite had no effect on T. canis eggs, thus confirming the results of Juris and Breza (1988). Likewise, at least 50% of the fertilized eggs preserved in 2% neutral formalin at 4°C for 21 months could fully embryonate and then have the same infectivity as embryonated fresh eggs (Chung et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CHUNG et al 30 observed a greater survival rate when the eggs were maintained at 4 o C. However, certain environmental factors can influence the evolution of Toxocara eggs in the soil 48,54 . Under experimental conditions, QUEIROZ et al 85 concluded that low temperatures, lack of luminosity and low levels of humidity are deleterious to the development of Toxocara canis eggs.…”
Section: Toxocara Canis Infection In Dogsmentioning
confidence: 99%